Characterisation of CMP‐Sialic Acid Transporter Substrate Recognition. Issue 15 (6th September 2013) - Maggioni, Andrea; von Itzstein, Mark; Rodríguez Guzmán, Ingrid Bibiana; Ashikov, Angel; Stephens, Alexandre S.; Haselhorst, Thomas; Tiralongo, Joe
<x xml:space="preserve">Abstract</x> CMP‐sialic acid transporter: We report an in‐depth, multidisciplinary, structural study that has identified the amino acid residues intimately involved in CMP‐sialic acid transporter (CST) substrate specificity. Our data provide a significant contribution towards a better understanding the structure–function relationship of this important family of transporters and the rational design of CST inhibitors.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>